2022
DOI: 10.3389/fcvm.2022.783739
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Functional Interplay of Nonhistone Lysine Crotonylome and Ubiquitylome in Vascular Smooth Muscle Cell Phenotypic Remodeling

Abstract: BackgroundThe crotonylation of histones is discovered of late as one of the post-translational modifications (PTMs) that can regulate gene expression. However, the function of crotonylation on nonhistone proteins in vascular smooth muscle cells (VSMCs) is unclear. Here, we aim to find the cellular characteristics of crotonylated nonhistone proteins and the cross talk with ubiquitinated proteins in VSMC phenotypic remodeling using the modified omics and proteomic analysis.MethodsWe performed the modified omics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…3A). In has been con rmed that enhanced glycolysis is closely related to PDGF-BBmediated phenotypic change of VSMC (Cao et al, 2022;Heiss et al, 2016). Then we screened mRNAs via microarray in PDGF-BB-challenged VSMCs transfected with Len-Con or Len-Mtmr7, and found that glucose metabolism-related pathway was signi cant downregulated after MTMR7 overexpression, indicating the MTMR7-mediated regulation of VSMC may involve the stability of glycolysis (Fig.…”
Section: Mtmr7 Inhibits the Phenotypic Switching Of Vsmc After Pdgf-b...mentioning
confidence: 87%
“…3A). In has been con rmed that enhanced glycolysis is closely related to PDGF-BBmediated phenotypic change of VSMC (Cao et al, 2022;Heiss et al, 2016). Then we screened mRNAs via microarray in PDGF-BB-challenged VSMCs transfected with Len-Con or Len-Mtmr7, and found that glucose metabolism-related pathway was signi cant downregulated after MTMR7 overexpression, indicating the MTMR7-mediated regulation of VSMC may involve the stability of glycolysis (Fig.…”
Section: Mtmr7 Inhibits the Phenotypic Switching Of Vsmc After Pdgf-b...mentioning
confidence: 87%
“… 78 Phenotypic changes in these VSMCs contribute to the remodeling of the vasculature. In one recent report, several non-histone proteins were identified as targets of Kcr within VSMCs, 79 with 2386 Kcr sites (570 proteins) and 2138 Kcr sites (534 proteins) in VSMCs that were or were not treated using PDGF-BB. Of these targets, the Kcr modification of 5 markers of VMSC contractility was detected at multiple sites, including 16 and 15 sites in caldesman1 and myosin9, respectively.…”
Section: The Biology Of Protein Crotonylationmentioning
confidence: 99%
“…We found that enzymes of the glucose metabolism pathways including glycolysis/gluconeogenesis, pentose phosphate pathway, pyruvate metabolism and TCA cycle, were modified extensively by crotonyl and ubiquitin. 20 The modification of the enzymes might modulate the pathways directly or indirectly. Among these enzymes, both the crotonylation and ubiquitination of LDHA were significantly increased in PDGF-BB-induced VSMCs, following that the expression of LDHA was also upregulated, thus we screen LDHA as an important enzyme that may regulate VSMC phenotypic switching.…”
Section: Ldha Expression Is Important For Vsmc Growth and Migrationmentioning
confidence: 99%
“…In our recent study, the interplay of non-histone lysine crotonylome and ubiquitylome in VSMCs phenotypic remodeling were analyzed through bioinformatics. 20 Given the potential link between glucose metabolism reprogramming and phenotypic switching of VSMCs, here we focused on the key enzymes of glucose metabolism. We find that crotonylation and ubiquitination of LDHA were significantly increased in PDGF-BB-induced proliferative VSMCs.…”
Section: Introductionmentioning
confidence: 99%